Cyber Justice - Mihr, Anja. author. aut Link
VIII, 89 p.
Keywords: This book introduces Cyber Justice as a viable approach for promoting good governance based on human rights norms in the internet. The author defines cyberspace as a borderless public space without common rules or government control mechanisms that protect and foster people’s activities within that space. In light of the growing scope of communications and interactions in the internet, the author shows how human rights and governance regimes can be adapted to cyberspace in order to ensure more accountability, transparency and interaction among those who use the internet and those who manage and provide internet services. This book will be of interest for scholars and policymakers interested in establishing governance regimes for cyberspace that will enjoy the support and trust of all users.